Sensory discrimination of chemical and temperature stimuli in the acoel Symsagittifera roscoffensis - Nikita Komarov; Christopher Aeschbacher; Laurent Sauterel; Evan Zuercher; Xavier Bailly; Pedro Martinez; Simon G. Sprecher (PLoS ONE, 2025)
Environmental cues provide critical sensory information for the survival of animals. Understanding how distinct sensory cues elicit or modulate certain behaviour thus provides insights into the adaptations to rapid and continuous changes in the surrounding world. Intertidal ecosystems are particularly exposed to environmental fluctuations. Due to changing exposure to seawater, animals are subjected to continuous fluctuations of temperature or salinity during the course of day-night and tidal cycles. Animals in intertidal environments show physiological and behavioural adaptations to these changes. Acoel worms constitute an important component of intertidal ecosystems. Symsagittifera roscoffensis, a well-studied species inhabiting the Atlantic coastline, has been extensively described in terms of its anatomy and development, yet its physiological responses remain poorly understood. When the acoel S. roscoffensis are exposed to daylight during the tidal cycle, these animals are found at the surface of sandy beaches, which enhance the exposure of their photosynthetic algal symbionts to light. Moreover, S. roscoffensis shows a strong positive phototaxis as well as both positive and negative geotaxis, both being evolved behavioural adaptations to enhance light exposure for its photosymbiont. Currently little is known about other sensory systems and their functions in this, or any other acoel worm. In this study, we probe sensory capabilities of S. roscoffensis focusing on chemical and temperature cues. Using two-choice and barrier assays, our findings support that S. roscoffensis shows avoidance behaviours to increased temperature and salinity, preferring cooler environments with lower salinity. We demonstrate that early branching bilaterians possess the sensory capacity to identify specific chemical and environmental stimuli, adding to the knowledge that may prove useful in understanding marine ecosystems in a period of global climate change that greatly affects aquatic environments.